Effort Estimation Model for Function Point Measurement - Koh, Tieng Wei (2007)
Software Cost Estimation is a practical process that is applied to find out basically the effort and development time requirements for a software product, which is going to be developed. The process starts with the planning phase activities and refined throughout the development. Various cost estimation models and methods are available to be used for software development process. The COCOMO, an algorithmic model is one example. Although it is hard to predict the exact size especially in terms of lines of code (LOC) of the project at the early stage, the COCOMO model takes LOC as an input to compute the project’s effort.